2019
DOI: 10.1029/2019jd031085
|View full text |Cite
|
Sign up to set email alerts
|

Ural Blocking Driving Extreme Arctic Sea Ice Loss, Cold Eurasia, and Stratospheric Vortex Weakening in Autumn and Early Winter 2016–2017

Abstract: This study investigates the dynamics that led to the repeated cold surges over midlatitude Eurasia, exceptionally warm conditions and sea ice loss over the Arctic, and the unseasonable weakening of the stratospheric polar vortex in autumn and early winter 2016–2017. We use ERA‐Interim reanalysis data and COBE sea ice and sea surface temperature observational data to trace the dynamical pathways that caused these extreme phenomena. Following abnormally low sea ice conditions in early autumn over the Pacific sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
60
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 63 publications
(67 citation statements)
references
References 58 publications
4
60
0
Order By: Relevance
“…The longer-lasting and larger magnitude of the central Eurasian winter cold anomalies could be related to a stronger weakening of westerly winds at midlatitude (second curves in Figures 4a and S4) due to deep warming over the Arctic which can lead to more persistence in weather patterns (Cohen et al, 2014;Francis & Vavrus, 2012) and in the UB (Luo et al, 2016). Though the influence of the UB on Arctic warming has also been suggested by some studies (Luo et al, 2016), we note that there are many different definitions of the Ural sector, which in some cases extend west to 10°W (Peings, 2019) or east to 100°E (Tyrlis et al, 2019). We do see dominant high-pressure anomalies over the Ural sector before and after the peaking of Arctic warming (in both shallow and deep warming cases) ( Figure S5).…”
Section: 1029/2020gl087212mentioning
confidence: 74%
“…The longer-lasting and larger magnitude of the central Eurasian winter cold anomalies could be related to a stronger weakening of westerly winds at midlatitude (second curves in Figures 4a and S4) due to deep warming over the Arctic which can lead to more persistence in weather patterns (Cohen et al, 2014;Francis & Vavrus, 2012) and in the UB (Luo et al, 2016). Though the influence of the UB on Arctic warming has also been suggested by some studies (Luo et al, 2016), we note that there are many different definitions of the Ural sector, which in some cases extend west to 10°W (Peings, 2019) or east to 100°E (Tyrlis et al, 2019). We do see dominant high-pressure anomalies over the Ural sector before and after the peaking of Arctic warming (in both shallow and deep warming cases) ( Figure S5).…”
Section: 1029/2020gl087212mentioning
confidence: 74%
“…For example, there is a connection between snow cover and the atmosphere. Air temperature forcing causes variability in snow cover extent in the Northern Hemisphere 54 , 55 , while changes in snow cover can affect the phase and amplitude of atmospheric circulations (e.g., AO/NAO/SH) 56 59 . However, there are still many challenges in understanding snow-atmosphere coupling 55 .…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al (2018) suggested that the cases of quasi-stationary UB events, a main factor for sea ice reduction via increased downward LW, have increased in the recent 2 decades. Tyrlis et al (2019) analyzed the impact of UB on the sea ice loss in the BKS in 2016-2017, showing that anomalous 2 m air temperature is related to warm and moist advection during UB events. Peings (2019) showed that imposing the UB pattern in November yields the WACE pattern with sea ice anomalies in the BKS.…”
Section: Introductionmentioning
confidence: 99%